ECOLOGICAL BASES OF FOLK ART - R. M. Abakarova; G. M. Gadzhinayev (Юг России: экология, развитие)
Abstract. Esthetic bases of natural in national culture is defined in the paper. On the example of construction and internal furniture of dwellings of peoples of Dagestan communication of microcosm and macrocosm in consciousness of people is shown. Architectural monuments of national culture kept features of adaptive-adapting function of ecological thinking of the people.Aim of the research is to define ecological bases of national architecture, to show features of natural and esthetic dwelling in the mountain regions of Dagestan.Methods of carrying out work represent interdisciplinary research of folk art in a context of cultural science, cultural history, and an esthetics. The complex of methods was used: diachronic, synchronic, functional, psychological.Main conclusions. National creativity is closely connected with the nature of the native land. So, lullabies and lyrical songs, games, signs, labor and ceremonial songs, and also architecture and painting reflected features of perception of nature by people, their attitude towards her, use of natural resources. In national creativity regional features of relationship of people and nature are most fully and authentically traced. In art of the people its spiritual wealth, the internal ecological environment is reflected.